Neurocognitive Sequelae in African American and Caucasian Children with MS - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Psychologists at the University of Alabama, Birmingham, examined neurocognitive differences between African American (AA) and Caucasian (CA) patients with pediatric-onset multiple sclerosis (POMS).